Proceedings of the 25th ACM SIGKDD International Conference on Knowledge Discovery &Amp; Data Mining 2019
DOI: 10.1145/3292500.3330704
|View full text |Cite
|
Sign up to set email alerts
|

Deep Uncertainty Quantification

Abstract: Weather forecasting is usually solved through numerical weather prediction (NWP), which can sometimes lead to unsatisfactory performance due to inappropriate setting of the initial states. In this paper, we design a data-driven method augmented by an effective information fusion mechanism to learn from historical data that incorporates prior knowledge from NWP. We cast the weather forecasting problem as an end-to-end deep learning problem and solve it by proposing a novel negative log-likelihood error (NLE) lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(25 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…A different approach estimates the forecast uncertainty directly from the data without requiring an a priori estimation of the forecast uncertainty, such as that provided by an ensemble of forecasts. D'Isanto and Polsterer (2018), Rasp and Lerch (2018), Wang et al (2018), Camporeale et al (2019), Barnes and Barnes (2021), and Veldkamp et al (2021) introduced NN architectures and training methodologies that directly quantify the uncertainty by performing the training over a large database of forecasts and their corresponding observations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A different approach estimates the forecast uncertainty directly from the data without requiring an a priori estimation of the forecast uncertainty, such as that provided by an ensemble of forecasts. D'Isanto and Polsterer (2018), Rasp and Lerch (2018), Wang et al (2018), Camporeale et al (2019), Barnes and Barnes (2021), and Veldkamp et al (2021) introduced NN architectures and training methodologies that directly quantify the uncertainty by performing the training over a large database of forecasts and their corresponding observations.…”
Section: Introductionmentioning
confidence: 99%
“…The key aspect is the definition of a loss function that should have a well-defined sensitivity to the state-dependent forecast uncertainty. Wang et al (2018) and Barnes and Barnes (2021) achieved this by defining a loss function inspired in the observation likelihood, whereas Camporeale (2018), D'Isanto andPolsterer (2018), Rasp and Lerch (2018), and Veldkamp et al (2021) defined a loss function based on the continuous ranked probability score and the Brier score. These studies concluded that this is a feasible approach for a cost-effective estimation of the forecast uncertainty for idealized and real-data cases.…”
Section: Introductionmentioning
confidence: 99%
“…To summarize, the uncertainty of physical system modeling can come from the following source. First, the initial and boundary condition of the physical system is non-deterministic, and the system may be chaotic, i.e., in weather forecasting, a small perturbation can introduce a large deviation in future prediction [139]. Second, the inherent physical principle may not be perfectly known or the parameter of the governing equation may be stochastic, i.e., in an imperfect physical system, the conservation law of heat may be violated in a non-closed system [148].…”
Section: Uq For Physics-aware Dnn Modelsmentioning
confidence: 99%
“…In the meantime, and, as the M4 competition was running, many new methods were introduced. Novel approaches were presented ranging from linear differential equations [27], regularized regression [28], and of course deep learning approaches like Deep Clustering [29], Recurrent Neural Networks [30], Deep Ensembles [31] , Attention Networks [32], and Convolutional Networks [33]. All these methods were applied in multiple application domains ranging from weather forecasting to pandemics.…”
Section: Conclusion and The Future Of Forecastingmentioning
confidence: 99%